Tectonic implications on the 2018 Hualien Earthquake - Strong Wen (Terrestrial, Atmospheric and Oceanic Sciences, 2019)

(untitled)
The 2018 Hualien earthquake occurred at the junction of the deformed continental crust of Eurasian plate and the Heping sea basin, where a northeast trending seismic belt exists. In this study, a 3D seismic tomographic inversion is used to investigate the seismogenic structures of the 2018 Hualien earthquake sequence. An earthquake relocation procedure is performed and the focal mechanisms are analyzed to study the faulting behavior. Our results indicate that the source region of the 2018 Hualien earthquake consists of complex high-angle eastward and westward dipping reverse faulting. We also observe that most earthquakes that have occurred in the area exhibit considerable variation in Vp/Vs ratios. Fluid migration may have played an essential role in causing the Vp/Vs ratio variation. We suggest that the mainshock of the 2018 Hualien earthquake may be associated with a west-dipping fault, which is a blind fault tending toward the Heping sea basin and possibly belonging to the Central Range fault system.